2022
DOI: 10.31234/osf.io/dv9cq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Drives the Association between Home Chaos and School Grades over Time? A Biometric Cross-Lagged Panel Approach

Abstract: Early exposure to home chaos relates to poor school performance. This is often interpreted as a causal influence in educational research, however underlying common genetic and environmental factors might affect both constructs, thus confound the effect. Genetics explain about 60% of variation in school performance, while (non-) shared environment constitutes the remaining variance. Also differences in home chaos – often considered an “environmental” factor – are partially influenced genetically. Thus, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…We hypothesized that cross-lagged paths from earlier educational achievement to later household chaos would mainly be due to E, because non-shared environmental influences drive changes in educational achievement (Rimfeld et al, 2018). Finding E influences on the cross-lagged paths would have suggested that effects of educational achievement on household chaos are likely to be causal (Malanchini et al, 2017;McAdams et al, 2020;Starr et al, 2022). Conversely, we predicted that cross-lagged paths from household chaos to educational achievement could be attributed to A and C influences, because these paths capture change that is due to child-driven processes in household chaos (Hannigan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that cross-lagged paths from earlier educational achievement to later household chaos would mainly be due to E, because non-shared environmental influences drive changes in educational achievement (Rimfeld et al, 2018). Finding E influences on the cross-lagged paths would have suggested that effects of educational achievement on household chaos are likely to be causal (Malanchini et al, 2017;McAdams et al, 2020;Starr et al, 2022). Conversely, we predicted that cross-lagged paths from household chaos to educational achievement could be attributed to A and C influences, because these paths capture change that is due to child-driven processes in household chaos (Hannigan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although parents' and children's reports of household chaos converge to some degree, there remains significant within-family variation the perception of household chaos. For example, in a UK population cohort sample, parents' and children's reports of household chaos correlated .53 and .55 when the children where 9 to 12 years old, respectively (N = 3,000 to N = 5,000; Hanscombe, Haworth, Davis, Jaffee, & Plomin, 2011), while in a German population cohort sample the correlation was .32 when children were 11 years old (N = 2,031; Starr, Ruks, Weigel & Riemann, 2022). Overall, perceptions of household chaos appear to vary over time and within families, suggesting that household chaos itself may constitute a modifiable environmental condition that affects children's educational achievement.…”
Section: Family Background: Rearing Environmentsmentioning
confidence: 97%
See 1 more Smart Citation